Determinación de las condiciones de operación de la planta de generación de vapor sobre parámetros de diseño (2019)
In the present work of degree, a computational model of the operation of the steam generation plant of the University of America was developed to carry out this project the Python program and its work environments Spyder and PyQt5 were used. For the elaboration of the model, first, a thermodynamic analysis of the cycle under which the plant operates, Superheated Rankine, was carried out. In this stage, the behavior of the process was examined point by point, through the result of the measurement of variables, such as temperature and pressure at the input and output of the equipment representative of the cycle. The objective of the study of these specific points is to obtain the thermodynamic properties of each of them, and then with this information, calculate the thermal efficiency of the cycle. Once the thermodynamic analysis was finished, we proceeded to write the code for the simulation of the plant in Spyder. In the model, the Python CoolProp library was used, which is in charge of searching and importing properties of multiple substances, within which is the water, which constitutes the working fluid of the cycle, in such a way, the structure of the code obtains the thermodynamic properties of each point of the process, through the input variables pressure and temperature, established by the user who makes use of this tool. To finalize the simulation, a graphic interface was designed in order to make the data entry more user friendly and the respective visualization of results, the development of this application was made in the PyQt5 work environment.